ENGINEERING SUPERVISORS’ PERCEPTION OF THE FINAL-YEAR PROJECT WRITING INSTRUCTION ON THE LEARNING MANAGEMENT SYSTEM - Shukor, Farhana; Mah, Boon Yih; Ul-Saufie, Ahmad Zia (Journal of Islamic, Social, Economics and Development, 2024)
It is typical to find more online courses globally during this endemic period with various technological tools available to support teaching and learning in higher education institutions. The Constructivist Learning Theory served as the foundation for this study as students used learning platforms to prepare their final year projects, building their knowledge based on experiences and social interactions. This study investigated how eight supervisors from four engineering faculties perceived the academic writing instruction provided to students completing their projects. Students must discuss their strategies and implementation with their supervisors to finish their final-year projects. The supervisors respond in semi-structured interview sessions on how utilising a learning management system (LMS) for final-year projects has several advantages, including improved content delivery, attendance tracking for record-keeping, assignment submission for evaluation, and discussion to boost participation. Difficulties include supervisors' lack of technical training utilising AI techniques, occasional limitations on follow-up activities, and poor engagement among interfaculty members. Supervisors can fulfil pedagogical requirements to guarantee that outcomes have been fully attained by closely modifying the steps to conduct language teaching and learning, especially to guide students on final-year projects. It is relevant because supervisors will help students apply what they have learned in the classroom to real-world problem-solving.